Implementation of Qanitat Values in Ulil Albab Female Students as a Foundation for Building a Household - Hanafi, Yusron; Asroriah, Fatimatul; Marsudiono, Agus (Instructional Development Journal, 2025)
This study investigates the integration of Qanitat values, encompassing spiritual depth, extensive knowledge, magnanimity, morality, and maturity, among female students in the Ulil Albab program as a crucial precursor to establishing stable and fulfilling house hold The research explores how these values, cultivated through Islamic religious education and the Ulil Albab character development strategies, equip female students with the essential competencies for navigating marital and familial responsibilities Through qualitative research methods, this study analyzes the specific pedagogical approaches and curriculum elements employed to instill these values, aiming to demonstrate their direct impact on the students' preparedness for future domestic roles. It further examines the students' perceptions of these values and their practical application within their daily lives and interactions within the pesantren environment, which serves as a vital training ground for developing the soft skills necessary for harmonious family life Ultimately, the findings aim to provide insights into effective strategies for cultivating well-rounded individuals who can contribute positively to their families and communities, reflecting the holistic approach of Islamic education in character building This comprehensive investigation seeks to identify and elaborate upon the specific educational methodologies and communal practices that foster these attributes, particularly within the unique context of female students preparing for future societal roles